EFFECT OF TREATMENT ANESTHETIC TACTICS ON LONG-TERM PAIN MANAGEMENT OUTCOMES IN PATIENTS WITH GUNSHOT AND MINE BLAST WOUNDS - Horoshko, V.R.; Kuchyn, Iu.L. (World of Medicine and Biology, 2024)
The frequency of chronic pain in patients after gunshot or mine blast wounds can range from 66 to 91.7 % and depends on several factors. However, the effect of therapeutic anesthesia tactics on long-term pain management outcomes in this category of patients remains unexplored. The results of pain management in 2215 patients with gunshot and mine blast wounds were analyzed. Comparisons were made using the Mann-Whitney and chi-squared tests with allowance for continuity. Better long-term results of pain management were in group 2 (p